Mainstreaming Eco-Theology: Practices and Challenges of Environmental Activism in Islamic Student Organizations in Indonesia - Rizqullah, Muhammad Naufan; Erman, Ery; Afandi, Muhamad Ridwan; Arifin, Jafar; Sidik, Ahmad Nur; Nisa Ulrifa (International Journal Scientific and Professional, 2025)
The environmental crisis presents a multidimensional challenge that is not only ecological but also moral and spiritual. In the context of Indonesia, Islamic student organizations hold strategic potential to play a role in environmental advocacy based on Islamic values. This study aims to examine the practice of eco-theological based environmental activism among Islamic student organizations, using a case study of the Indonesian Muslim Student Action Union (Kesatuan Aksi Mahasiswa Muslim Indonesia/KAMMI). Data were collected through interviews, observations, literature reviews, and document analysis of environmental programs carried out by the organization. The results show that although environmental issues have yet to become a priority agenda, there are several initiatives by KAMMI contributing to environmental preservation. The study found that the main challenges in mainstreaming eco-theology are the lack of Islamic-based environmental literacy and the dominance of socio-political issues in student movements. These findings recommend the integration of eco-theological content into the organization's cadre training curriculum and the strengthening of networks with environmental communities.